2010
DOI: 10.1111/j.1743-6109.2009.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Vardenafil can Improve Continence Recovery after Bilateral Nerve Sparing Prostatectomy: Results of a Randomized, Double Blind, Placebo-Controlled Pilot Study

Abstract: Introduction Phosphodiesterase type 5 inhibitors (PDE5-I) have acquired an established role in the treatment of post-prostatectomy erectile dysfunction (ED). Several trials in men with ED and lower urinary tract symptoms associated with benign prostatic hyperplasia suggest that PDE5-I could improve both erectile function and urinary symptoms. Aim To assess the role of vardenafil in continence recovery after bilateral nerve sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…2) and in the vardenafil trial by Gacci and colleagues. 4 It certainly is possible that there are differences between the effects of sildenafil and vardenafil on urinary convalescence after RP, but the similar data that resulted from our study, the Gacci study and previous reports using short-acting PDE5i post-RP all suggest that these drugs act very similarly in this setting. 18 Pertinently, Bittencourt and colleagues recently demonstrated that sildenafil relaxes human bladder tissue depending on the nitric oxide/cGMP pathway.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…2) and in the vardenafil trial by Gacci and colleagues. 4 It certainly is possible that there are differences between the effects of sildenafil and vardenafil on urinary convalescence after RP, but the similar data that resulted from our study, the Gacci study and previous reports using short-acting PDE5i post-RP all suggest that these drugs act very similarly in this setting. 18 Pertinently, Bittencourt and colleagues recently demonstrated that sildenafil relaxes human bladder tissue depending on the nitric oxide/cGMP pathway.…”
Section: Discussionsupporting
confidence: 63%
“…The authors reported improvements in urinary function and bother in patients taking nightly vardenafil compared to those taking it ondemand or taking placebo during the months after RP. 4 However, this improvement was entirely dependent on a significantly greater initial decline in urinary function and bother in the nightly vardenafil group, and a subsequent improvement from that state of decreased urinary function over time. Indeed by 12 months, urinary outcomes were equivalent in all groups, so another interpretation of their data is that nightly vardenafil delays urinary recovery until the first postoperative year.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…28 We also showed that the continence recovery after nerve-sparing prostatectomy for PCa was strictly correlated with recovery of SF: thus, we concluded that PDE5 inhibitors can exhibit an activity in the lower urinary tract, even in the absence of the prostatic gland, by a pathway not including prostate. 29 Therefore, the androgen-dependent PDE5 activity of the bladder wall can explain the significant correlation between erectile function and urinary symptoms exclusively in patients with adequate T. In our experience, this activity can be provided both by the relaxation of the smooth muscle and by the improvement in perfusion of the bladder wall. 30 …”
Section: Discussionmentioning
confidence: 80%